2007
DOI: 10.1089/ars.2006.1517
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Misfolded Protein Through Nitrosative Stress Linked to Neurodegenerative Disorders

Abstract: Protein quality control is a critical feature of intracellular homeostasis. In particular, unfolded or misfolded proteins resulting from environmental stresses or free radicals are rapidly degraded via the ubiquitin-proteasome pathway. Nitric oxide (NO), a free radical gas, has been reported to be involved in such processes as vasorelaxation and neurotransmission. Conversely, NO also is implicated in neuronal cell death or neurodegeneration. Recent reports suggest that S-nitrosylation of proteins is a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 45 publications
0
44
0
Order By: Relevance
“…In brains manifesting sporadic Parkinson's or Alzheimer's disease, Snitrosylation inhibits PDI's enzymatic activity, leading to the accumulation of polyubiquitinated proteins, which activates the unfolded protein response (Uehara et al, 2006). Activation of this stress pathway, may be linked to the development of sporadic neurodegenerative diseases (Uehara, 2007). Snitrosylation of parkin also eventually leads to the accumulation of unfolded proteins and subsequent neuronal cell death ).…”
Section: No Functions In Immunity and Neurodegenerative Diseasementioning
confidence: 99%
“…In brains manifesting sporadic Parkinson's or Alzheimer's disease, Snitrosylation inhibits PDI's enzymatic activity, leading to the accumulation of polyubiquitinated proteins, which activates the unfolded protein response (Uehara et al, 2006). Activation of this stress pathway, may be linked to the development of sporadic neurodegenerative diseases (Uehara, 2007). Snitrosylation of parkin also eventually leads to the accumulation of unfolded proteins and subsequent neuronal cell death ).…”
Section: No Functions In Immunity and Neurodegenerative Diseasementioning
confidence: 99%
“…PDI has been shown to accumulate with neurofibrillary tangles and the dystrophic neurites of senile plaques in AD brain, and with FUS-positive ubiquitinated inclusions in human ALS patient spinal cords (107,108). Not only was there an increase in PDI expression in AD, PD, and ALS brain, the amount of S-nitrosylated PDI was also substantial (107,(109)(110)(111)(112)(113)(114)(115). S-nitrosylation of PDI, through the redox-active thiols of the a and a' domains, inhibits enzyme activity.…”
Section: The Role Of Hbcat In Protein Folding and Redox-chaperone Actmentioning
confidence: 99%
“…Several studies reported the involvement of excess generation of NO and its adducts in the etiology of multiple disease states, including insulin resistance and diabetes, atherosclerosis or Alzheimer's disease [Duplain et al, 2008;Parastatidis et al, 2007;Uehara, 2007;Yasukawa T et al, 2005;White et al, 2010].…”
Section: Nitrogen Centered Radical Species (Rns)mentioning
confidence: 99%